MEASURING PUBLIC ASSET PERFORMANCE USING OUTPUTBASED APPROACH: EVIDENCE FROM INDONESIA - Puspitarini, Intan; Akhmadi, Muhammad Heru (PLANNING MALAYSIA, 2019)
Indonesia’s Central Government 2016 Fiscal Year Financial Report shows that the proportion of the total value of public assets owned by the Central Government (known as State-Owned Assets/SOAs) was very significant to the total value of its asset in the balance sheet, which was 40%. While the total value of SOAs sat on IDR 2,200 trillion, the total asset in the balance sheet reached IDR 5,456.88 trillion. Such significant value of SOAs consequently requires the Indonesian government to develop an asset management strategy to effectively and efficiently manage SOA. The utilization of SOAs is one of the tools employed by the government to ensure that capital expenditures spent have been fitted to their intended use. With this premise, it is important for the Government to measure the performance of SOAs. The purpose of this study is to derive a simple and convenient equation using output-based approach to measure SOAs performance that may be used as a reference for the government in devising its policies. This research used the qualitative method with literature study and field testing through a study case. The research object is limited to SOAs in the form of office buildings. The results indicate that measuring SOAs performance using the proposed formula is applicable to SOAs in Indonesia, particularly those in the form of office buildings. Through such performance assessment, the potential of idle assets is expected to be minimized, and public asset planning process becomes more efficient by creating several alternative cost requirements over a certain period of planned asset output.